Oncology nurses' perceptions of advance directives for patients with cancer. (5th April 2021) - Hobden, Breanne; Bryant, Jamie; Waller, Amy; Shepherd, Jan; Sanson‐Fisher, Rob
Abstract: This study examined oncology nurses' perceptions of the impact of advance directives on oncology patients' end‐of‐life care. Nurses ( n  = 104), who were members of an oncology nursing society or worked in a large metropolitan cancer center, completed a cross‐sectional survey assessing perceptions of advance directives. There was high agreement that advance directives (i) make decisions easier for family (87%) and providers (82%); (ii) are doctors' responsibility to implement (80%); (iii) reduce unwanted aggressive treatment in the last weeks of life (80%); (iv) protect patient autonomy (77%); and (v) increase the likelihood of dying in a preferred location (76%). There was moderate or low agreement that advance directives (i) are accessible when needed (60%); (ii) are oncology nurses' responsibility to implement (46%); (iii) are always followed (41%); (iv) reduce the likelihood of pain in the last weeks of life (31%); (v) contain difficult to follow statements (30%); and (vi) have no impact on comfort in the last weeks of life (15%). Most nurses perceive benefits for advance directives, however, there remains uncertainty around accessibility and implementation. Guidelines and education about advance directive processes in oncology could improve person‐centered end‐of‐life care.